PENERAPAN STRATEGI STAD DALAM PEMBELAJARAN DRAMA DI SMP NEGERI 1 JATEN KABUPATEN KARANGANYAR - SRI PURWANTI (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2022)
The purpose of this study was to describe the STAD strategy in learning drama in class VIII H SMP Negeri 1 Jaten in terms of (1) lesson planning; (2) application in learning; (3) obstacles in learning; and (4) the solution. This research is a qualitative descriptive study. The subjects of this research were teachers and students of class VIII H SMP Negeri 1 Jaten Karanganyar. The research data is in the form of qualitative data with data sources from teachers, students, learning processes, and learning documents. The strategy in this research is a case study. Data collection techniques are interviews, observation, document analysis, and tests. Data validity technique with source triangulation. Data analysis technique with interactive analysis. The results showed that (1) STAD strategic planning in drama learning for grade VIII H students of SMP Negeri 1 Jaten Karanganyar Regency had been well prepared. (2) Implementation of STAD strategy in drama learning for class VIII H students of SMP Negeri 1 Jaten Karanganyar Regency. Make students active and work together to solve a problem. (3) The obstacles to implementing the STAD strategy are as follows. (a) Less than optimal implementation of the STAD strategy. (b) Students do not understand the STAD learning steps. (c) There are students who are conversing. (d) Limited time. there are students who are less active. (f) There are students who are busy when they go to their groups. (g) There are students who do not want to read examples of drama texts. (h) There are some groups that have not yet submitted assignments. (i) the dominance of certain students during the discussion. (j) the contribution of low achieving students is less. (k) The cooperative nature of students is still lacking. Solutions to overcome these obstacles. (a) The teacher optimizes the implementation of the STAD strategy. (b) The teacher learns the STAD strategy learning steps. (c) The teacher controls the class. (d) The teacher designs learning by managing time efficiency. The teacher gives motivation to students. (f) Teachers and students Make additional rules. (g) The teacher gives examples of drama texts that attract students' interest and attention. (h) The teacher controls each group by asking what are the difficulties faced by students. (i) Teachers have more references regarding the importance of group learning in doing assignments. (j) Teachers motivate students who have low achievement. (k) The teacher guides students more to work together. ABSTRAKTujuan dalam penelitian ini adalah untuk mendeskripsikan strategi STAD dalam pembelajaran drama pada siswa kelas VIII H SMP Negeri 1 Jaten dari segi (1) perencanaan pembelajaran; (2) penerapan dalam pembelajaran; (3) kendala dalam pembelajaran; dan (4) solusinya. Penelitian ini merupakan penelitian deskriptif kualitatif. Sebagai subjek penelitian ini adalah guru dan siswa kelas VIII H SMP Negeri 1 Jaten Karanganyar. Data penelitian berupa data kualitatif dengan sumber data guru, siswa, proses pembelajaran, dan dokumen pembelajaran. Strategi dalam penelitian ini studi kasus terpancang. Teknik pengumpulan data dengan wawancara, observasi, análisis dokumen, dan tes. Teknik validitas data dengan triangulasi sumber. Teknik análisis data dengan análisis interaktif. Hasil penelitian menunjukkan bahwa (1) Perencanaan strategi STAD dalam pembelajaran drama bagi siswa kelas VIII H SMP Negeri 1 Jaten Kabupaten Karanganyar sudah dipersiapkan dengan baik. (2) Penerapan strategi STAD dalam pembnelajaran drma bagi siswa kelas VIII H SMP Negeri 1 Jaten Kabupaten Karanganyar Membuat siswa aktif dan bekerja sama untuk memecahkan suatu masalah. (3) Kendala penerapan strategi STAD sebagai berikut. (a) Kurang optimalnya penerapan strtegi STAD. (b) Siswa kurang memahami langkah pembelajaran STAD. (c) Terdapat siswa yang bercakap-cakap. (d) Keterbatasan waktu. terdapat siswa yang kurang aktif. (f) Terdapat siswa yang ramai saat menuju ke kelompoknya. (g) Terdapat siswa yang tidak mau membaca contoh teks drama. (h) Terdapat sebagian kelompok yang sampai batas akhir belum mengumpulkan tugas. (i) dominaso siswa tertentu saat diskusi. (j) kontribusi dari siswa berprestasi rendah kurang. (k) Sifat suka bekerja sama dari siswa masih kurang. Solusi mengatasi kendala tersebut. (a) Guru mengoptimalkan penerapan strategi STAD. (b) Guru mempelajari langkah pembelajaran strategi STAD. (c) Guru menguasai kelas. (d) Guru merancang pembelajaran dengan mengatur efisiensi waktu. Guru memberikan motovasi kepada siswa. (f) Guru dan siswa Membuat aturan tambahan. (g) Guru memberikan contoh teks drama yang menarikminat dan perhatian siswa. (h) Guru melakukan control terhadap setiap kelompok dengan menanyakan apa saja keulitan yang dihadapi siswa. (i) Guru lebih banyak referensi terkait pentingnya belajar kelompok dalam mengerjakan tugas.(j) Guru memotivasi siswa yang berprestasi rendah. (k) Guru lebih banyak membimbing siswa untuk bekerja sama.